2017
DOI: 10.1093/aje/kww104
|View full text |Cite
|
Sign up to set email alerts
|

Validity of a Dietary Questionnaire Assessed by Comparison With Multiple Weighed Dietary Records or 24-Hour Recalls

Abstract: The authors evaluated the validity of a 152-item semiquantitative food frequency questionnaire (SFFQ) by comparing it with two 7-day dietary records (7DDRs) or up to 4 automated self-administered 24-hour recalls (ASA24s) over a 1-year period in the women's Lifestyle Validation Study (2010-2012), conducted among subgroups of the Nurses' Health Studies. Intakes of energy and 44 nutrients were assessed using the 3 methods among 632 US women. Compared with the 7DDRs, SFFQ responses tended to underestimate sodium i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
269
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 355 publications
(279 citation statements)
references
References 31 publications
7
269
2
1
Order By: Relevance
“…Although gluten has not been specifically quantified in validation studies of food frequency questionnaires, this instrument has shown good validity with regard to reasonable correlation with seven day dietary recall of foods containing gluten (supplementary table A) and intake of vegetable protein, to which gluten is a significant contributor. 29 In addition, participants with undiagnosed celiac disease were not uniformly identified in these cohorts. However, according to population based estimates, such people would account for less than 1% of the cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although gluten has not been specifically quantified in validation studies of food frequency questionnaires, this instrument has shown good validity with regard to reasonable correlation with seven day dietary recall of foods containing gluten (supplementary table A) and intake of vegetable protein, to which gluten is a significant contributor. 29 In addition, participants with undiagnosed celiac disease were not uniformly identified in these cohorts. However, according to population based estimates, such people would account for less than 1% of the cohort.…”
Section: Discussionmentioning
confidence: 99%
“…27 28 A separate validation study of this food frequency questionnaire found that this method of measuring vegetable (that is, plant based) protein intake, of which gluten is the major contributor, correlated highly with that measured in seven day dietary records (Spearman correlation coefficient 0.66). 29 We divided cohort participants into fifths of estimated gluten consumption, according to energy adjusted grams of gluten per day. We obtained energy adjusted values by regression using the residual method, as described previously.…”
Section: Measurement Of Exposure and Outcomementioning
confidence: 99%
“…This strategy aimed at minimizing errors of interpretation and response. It is also worth noting that the use of a FFQ, as a method to assess food consumption, tends to overestimate the reported consumption [43]. However, this tendency of overestimating makes the presence of a risk factor even more evident among those who were classified as having a non-regular consumption of fruits and vegetables, which is considered a marker of a healthy diet.…”
Section: Discussionmentioning
confidence: 99%
“…All foods and nutrients were energy adjusted using the residual method (20). The validity and reliability of the FFQs have been previously described (2124). Previous validation studies in subsets of participants have shown that FFQ-derived estimates of energy-adjusted intakes of magnesium, fiber, and total carbohydrate are moderately to strongly correlated with diet record–derived reports (magnesium, r = 0.61–0.73; fiber, r = 0.63–0.68; total carbohydrate, r = 0.65–0.73) (22,24).…”
Section: Methodsmentioning
confidence: 99%